(Re)thinking environmental governance in the changing climate context of northwestern Ghana - Osei-Amponsah, Charity; Okem, Andrew; Nornoo, J.; Puopiel, F. (Leiden University Press, 2025)
This chapter investigates the intersection of gender, generation, and agricultural livelihoods in the context of environmental governance. Through a case study in the Upper West Region of Ghana, it explores how climate change impacts are shaped by both gender and generational factors, with power relations and inequalities deeply embedded within environmental decision-making processes. The chapter offers new perspectives on the intricate relationships between institutions, structures, and processes in governing climate resilience. It argues that recognising the interconnectedness of gender and generation, and how these intersect with building climate resilience, offers valuable insights for environmental governance, particularly in co-designing inclusive and fit-for-purpose interventions. Achieving effective governance requires sufficient human and financial resources from the government, development partners, and other relevant stakeholders. Mainstreaming gender and generational considerations into environmental governance necessitates enhancing inclusive decision-making to shape social and ecological outcomes, as well as promoting the active participation of women, men, younger and older generations in decision-making processes.